Indigo Adult Adjustment - Hafidzah Rahmah Adi Setia Putri; Riza Noviana Khoirunnisa (Universitas Negeri Surabaya, 2023)
This study aims to describe the process of adjustment in indigo adults and the factors that influence the adjustment in indigo adults. This research uses a qualitative approach with a case study method. The participants in this study were three indigo individuals who reached middle adulthood. Data collection was carried out through semi-structured interviews using data analysis from Miles and Hubarman. Test the validity of the data using member checking. The results of the study showed that the three participants had different descriptions of the adjustment process. In the adjustment of indigo adults, two indigo adults were able to achieve adjustment because they could achieve the process of self-acceptance and one other indigo was unable to achieve adjustment because they could not achieve the process of self-acceptance, felt disturbed by their sixth sense abilities, and were unable to control emotions. The process of adjustment to indigo adults is jointly influenced by factors which include physical conditions, development and maturity, psychological conditions, and environmental conditions. Key word : Adjustment, Indigo, Maturity